A review on clonal regeneration of rubber (Hevea brasiliensis müll. Arg) / Nur’ Fatihah Mohamed - Mohamed, Nur’ Fatihah (Faculty of Plantation and Agrotechnology, 2018)
Rubber (Hevea brasiliensis Müll. Arg) is one of our major crops in Malaysia which has been established in agricultural sector for years. Other than for its latex, rubber also have opportunity in timber industry. According to Ching (2017), the demand of rubber will be increased by 10% in the future and we need to make sure our supply is enough to fulfil global demand. With our current biotechnology, plant tissue culture technology is used to produce high quality clonal planting materials for most of our major crops including rubber. However, it is considered challenging as rubber is always been persistent to phase change and slow response to the media (Moradpour, 2016). This review is to find out the effect of each plant growth regulators and the best nutrient medium combination in tissue culture of rubber. The morphological growth varies in term of shoot, leaves and roots just by regulating the medium by adding different additives such as hormones. The induction of their morphological growth in term of shoot, leaves and roots are identified by regulating the selected medium with different types and concentrations of plant growth regulators. In this review, the best combination of PGRs for clonal rubber with well-developed taproots is MS medium added with 0.075 mg/L BAP and 0.001 mg/L NAA established by Dickson et al., (2011) and for the highest somatic embryogenesis induction is 1.0 mg/L KN and 0.2 mg/L BA established by Zhou et al., (2010). Even though no commercial application of plant tissue culture in rubber yet, this review should be developed and new improvement may also increase the research and development of plant tissue culture of rubber.